1966
DOI: 10.1111/j.1469-1809.1966.tb00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aspects of angiokeratoma corporis diffusum

Abstract: Summary The genetic data on two new families with angiokeratoma corporis diffusum are recorded. The first pedigree extends over five generations. Six males are known to be affected in the three most recent generations, and possibly three more in the two previous ones. The mode of inheritance is consistent with a sex‐linked gene. This is confirmed by the occurrence of colour blindness and informative Xga findings in one section of the family, suggesting that the angiokeratoma locus may lie between those for Xg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1968
1968
2000
2000

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…1, angiokeratoma corporis diffusum affects males and is inherited as an X-linked recessive. The evidence, which we have reviewed elsewhere (Johnston et al, 1966), is strongly in favour of the gene for angiokeratoma corporis diffusum being on the X chromosome, and it may lie between the loci for colour blindness and the blood group Xg (a). Opitz et al (1965) in their review also concluded that the disease was X-linked.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…1, angiokeratoma corporis diffusum affects males and is inherited as an X-linked recessive. The evidence, which we have reviewed elsewhere (Johnston et al, 1966), is strongly in favour of the gene for angiokeratoma corporis diffusum being on the X chromosome, and it may lie between the loci for colour blindness and the blood group Xg (a). Opitz et al (1965) in their review also concluded that the disease was X-linked.…”
Section: Discussionmentioning
confidence: 89%
“…J0rgensen and J0rgensen (1965) reported such a patient with recurrent episodes beginning at the age of 20. Brown and Milne (1952), Duperrat (1959), Curry and Fleisher (1961), Wise et al (1962), and Johnston, Warland, and Weller (1966) all recorded further patients in whom cerebrovascular accidents had occurred between the ages of 18 and 30. The brain-stem seems particularly liable to involvement.…”
Section: Discussionmentioning
confidence: 99%
“…It is very uncommon for heterozygous females to have major clinical manifestations [5], and they are usually asymptomatic [2, 6]. The most frequent clinical findings in females are the characteristic whorl-like corneal opacities [2].…”
Section: Discussionmentioning
confidence: 99%
“…Initial linkage data suggest location of the alpha-GAL locus within measurable distance of Xq [Opitz et al, 1965;Johnston et al, 1966;Johnston and Sanger, 198 11. However, deGroot et a1 [ 19781 reevaluated the data and concluded that the evidence was weak.…”
Section: Genetic Considerations Dr John M Opitz Adjunct Professor mentioning
confidence: 99%